Using Bookwidgets to Attract Students' Interest in Learning English - Zaitun Zaitun; Muhammad Sofian Hadi; Diah Rahmawati Lestari (Journal of Languages and Language Teaching, 2021)
English teachers deliver their teaching materials using various platforms. One of those is the BookWidgets platform which is used to create interactive learning activities and involves students in engaging teaching material. This platform provides teachers and students with dynamic widgets such as iPad, Android tablets, Chromebooks, and iBooks with interactive content. These are designed to interact with students’ interest in acquiring English smoothly. Therefore, this study is aimed at finding out students’ interest in learning English and attract their interest using Bookwidgets. The method used in this study was a quantitative descriptive method, which used a survey to collect the data. The population in this study was taken from junior high school students in MTs Al-Falah using a questionnaire or online survey. In analyzing the data, the writer used a Likert statistical analysis. The results of this showed that students’ interest in English learning using media increased up to 48,1% after they were being introduced to Bookwidgets.